International financial reporting standards in the MENA region : adaptation and application in Morocco - Benhayoun, Issam (New York : Routledge, 2025)
"In the ever-evolving landscape of global economics, accounting stands as the universal language of business. This book explores the vital role of accounting in articulating economic, social, and environmental activities. It provides a detailed comparison between Moroccan GAAP, IFRS, and US GAAP, highlighting the challenges and opportunities of harmonizing accounting standards in the context of Morocco's unique business environment. Each chapter is crafted to offer practical guidance and technical insights. From property, plant, and equipment (IAS 16) to intangible assets (IAS 38), leases (IAS 17), and inventory valuation (IAS 2), the book covers essential standards with a focus on their real-world application. Special emphasis is placed on the preparation of cash flow statements (IAS 7), a crucial aspect often overlooked in the Moroccan accounting framework. Through practical case studies and comparative analyses, readers will gain a comprehensive understanding of the principles governing financial statements and the importance of transparency and investor confidence. This book is an indispensable resource for accounting professionals, academics, and anyone interested in the global standardization of financial reporting"--
Keywords: International financial reporting standards; Accounting -- Standards -- Morocco; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / Auditing